Antibacterial Evaluation of Gallic Acid and its Derivatives against a Panel of Multi-drug Resistant Bacteria - Mohamed, Abdella; Lahiri, Chandrajit *; Iskandar, Abdullah; Ayaz, Anwar * (Bentham Science Publishers, 2024)
Background: Infectious diseases are the second leading cause of deaths worldwide. Pathogenic bacteria have been developing tremendous resistance against antibiotics which has placed an additional burden on healthcare systems. Gallic acid belongs to a naturally occurring phenolic class of compounds and is known to possess a wide spectrum of antimicrobial activities.